2003
DOI: 10.1016/s1443-8461(03)80015-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of muscle energy technique on hamstring extensibility: the mechanism of altered flexibility

Abstract: Purpose: To investigate the effectiveness of muscle energy technique in increasing passive knee extension and to explore the mechanism behind any observed change.Procedure: 40 asymptomatic subjects were randomly allocated to control or experimental groups. Subjects lay supine with their thigh fixed at 90° flexion, and the hamstring muscle stretched to the onset of discomfort by passive knee extension. Knee range of motion was recorded with digital photography and passive torque recorded with a hand-held dynamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 21 publications
3
88
0
1
Order By: Relevance
“…10 MET has been relatively unexplored, with only a few published studies 1,20,28,38,39,41,51 supporting its use for cervical, lumbar, and thoracic motion restrictions. 20,28,38,39,51 Only 3 identified studies have investigated the use of MET for the lower extremity, 1,40,41 and none for the upper extremity. The purpose of this study was to compare the immediate effects of an MET applied to the GHJ horizontal abductors and an MET applied to the GHJ external rotators on improving GHJ horizontal adduction and GHJ internal rotation ROM in baseball players without shoulder pathology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 MET has been relatively unexplored, with only a few published studies 1,20,28,38,39,41,51 supporting its use for cervical, lumbar, and thoracic motion restrictions. 20,28,38,39,51 Only 3 identified studies have investigated the use of MET for the lower extremity, 1,40,41 and none for the upper extremity. The purpose of this study was to compare the immediate effects of an MET applied to the GHJ horizontal abductors and an MET applied to the GHJ external rotators on improving GHJ horizontal adduction and GHJ internal rotation ROM in baseball players without shoulder pathology.…”
Section: Methodsmentioning
confidence: 99%
“…While improvements have been reported using MET on the cervical, thoracic, and lumbar spine, 20,28,38,39,51 only 2 studies have investigated MET use in the extremities. 1,41 Following a single application of MET to the hamstring muscles, Ballantyne et al 1 observed a significant increase in passive knee extension. Smith and Fryer 41 reported significant increases in hamstring flexibility following 2 applications of MET performed over a 2-week period.…”
mentioning
confidence: 99%
“…The present study aimed to determine the effectiveness of postisometric relaxation over the isometric exercises in non-specific neck pain, yet there is dearth of clinical trials related to the effectiveness of postisometric relaxation (Cassidy and Lopes, 1992;Bentley, 1996;Schnek and MacDiarmid, 1997;Fryer, 2000;Ballantyne & Fryer, 2003;Lenehan & Fryer, 2003;Wilson & Payton, 2003;Fryer and Ruszkowski, 2004;Denise et al, 2006). No randomized controlled trial examining the outcomes of this treatment in symptomatic populations has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, these effects seemed to last only a few seconds to minutes, indicating that for continued benefit, MET would have to be applied multiple times throughout the day 7 . At present, the treatment window and lasting effect of a single MET session is undefined 1,2,[4][5][6][7][8][9][10][11] . Evidence to support the use of lumbar manipulation in patients with acute lumbopelvic pain with moderate severity has been reported 12,13 , yet, because the treatment pattern of manually trained clinicians varies, we were interested to determine if MET offered similar benefits (albeit, short-term) in patients with acute LPP.…”
mentioning
confidence: 99%